Synthesis of graphene oxide and green properties of dry pressed alumina compacts with small addition of graphene oxide/graphite - Pandey V.; Mohanta K.; Kumar A.; Yadav M.K.; Gupta A. (My University, 2025)
In the present study, graphene oxide (GO) was synthesized by modified Hummers method, and the synthesized GO was characterized and confirmed by XRD, TEM and FTIR analysis. The effect of small (0–1.5 wt%) addition of synthesized GO on the properties of dry pressed green alumina (Al2O3) compacts was studied. The compaction and packing behaviour was correlated with the density and microstructure of green compacts. Observed results were compared with the properties of green samples prepared with small (0–3 wt%) addition of graphite (Gr). The experimental results revealed that the density of green alumina compacts increased with the addition of GO/Gr powder up to an optimum amount beyond which a decrease in density was observed at all compaction loads. The green densities of Al2O3-GO compacts and Al2O3-Gr compacts were in the range 75–85% theoretical density (TD) and 60–65% TD, respectively. Observed results were confirmed from the SEM micrographs of corresponding green compacts. © 2020, Australian Ceramic Society.